Well Posedness of A Common Coupled Fixed Point Problem - Aydi, Hassen; Abbas, Mujahid (Communications in Mathematics and Applications, 2018)
In this paper, we prove rst some common coupled xed point theorems for mappings \(T : X × X→ X\) and \(g : X → X\) satisfying a generalized contractive condition on a metric space. We provide examples of new concepts introduced herein. We also study the well posedness of a common coupled xed point problem. Our results generalize several well known comparable results in the literature.